A two-parameter Budyko function to represent conditions under which evapotranspiration exceeds precipitation - P. Greve; L. Gudmundsson; B. Orlowsky; S. I. Seneviratne (Hydrology and Earth System Sciences, 2016)
A comprehensive assessment of the partitioning of precipitation (P) into evapotranspiration (E) and runoff (Q) is of major importance for a wide range of socio-economic sectors. For climatological averages, the Budyko framework provides a simple first-order relationship to estimate water availability represented by the ratio E / P as a function of the aridity index (Ep∕P, with Ep denoting potential evaporation). However, the Budyko framework is limited to steady-state conditions, being a result of assuming negligible storage change in the land–water balance. Processes leading to changes in the terrestrial water storage at any spatial and/or temporal scale are hence not represented. Here we propose an analytically derived modification of the Budyko framework including a new parameter explicitly representing additional water available to evapotranspiration besides instantaneous precipitation. The modified framework is comprehensively analyzed, showing that the additional parameter leads to a rotation of the original water supply limit. We further evaluate the new formulation in an example application at mean seasonal timescales, showing that the extended framework is able to represent conditions in which monthly to annual evapotranspiration exceeds monthly to annual precipitation.